All solid state battery

JP7639664B2Active Publication Date: 2025-03-05TOYOTA JIDOSHA KK
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021187654
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-11-18
Publication Date
2025-03-05
Estimated Expiration
2041-11-18

AI Technical Summary

Benefits of technology

【0015】 本開示においては、内部抵抗の増加を抑制した全固体電池を提供することができるという効果を奏する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007639664000003
    Figure 0007639664000003
  • Figure 0007639664000004
    Figure 0007639664000004
  • Figure 0007639664000005
    Figure 0007639664000005
Patent Text Reader

Abstract

To provide an all-solid battery in which an increase of an inner resistance is suppressed.SOLUTION: In the present disclosure, an all-solid battery is provide, comprising: a positive electrode; a negative electrode; and a solid electrolyte layer arranged between the positive electrode and the negative electrode. The negative electrode has a negative electrode active material layer and a negative electrode collector. The negative electrode active material layer contains: a negative electrode active material; a sulfide solid electrolyte; a molten salt having a melting point of 30°C or higher and 80°C or lower. The negative electrode collector is a collector in which a sulfide reaction occurs by the sulfide solid electrolyte.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to all-solid-state batteries. [Background technology]

[0002] An all-solid-state battery is a battery having a solid electrolyte layer between a positive electrode and a negative electrode, and has the advantage that it is easier to simplify the safety device compared to a liquid-based battery having an electrolyte solution containing a flammable organic solvent. The negative electrode usually has a negative electrode current collector and a negative electrode active material. Patent Document 1 discloses a negative electrode for an all-solid-state battery using nickel foil as a negative electrode current collector. Patent Document 1 also discloses that the negative electrode active material contains a solid electrolyte such as a sulfide solid electrolyte, an oxide solid electrolyte, or a polymer electrolyte. On the other hand, a molten salt with good ionic conductivity and electronic conductivity is known. For example, Patent Document 2 discloses a molten salt containing a specific first imidazolium salt and a specific second salt. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2020-177904 A [Patent Document 2] International Publication No. 2011 / 074325 Summary of the Invention [Problem to be solved by the invention]

[0004] Among solid electrolytes, sulfide solid electrolytes have the advantage of high ionic conductivity. On the other hand, when the negative electrode active material layer contains a sulfide solid electrolyte, the sulfide solid electrolyte may react with the negative electrode current collector, causing the negative electrode current collector to be sulfurized. When the negative electrode current collector is sulfurized, the internal resistance increases and the battery performance decreases.

[0005] The present disclosure has been made in consideration of the above-mentioned circumstances, and has as its main object to provide an all-solid-state battery in which an increase in internal resistance is suppressed. [Means for solving the problem]

[0006] The present disclosure provides an all-solid-state battery having a positive electrode, a negative electrode, and a solid electrolyte layer disposed between the positive electrode and the negative electrode, wherein the negative electrode has a negative electrode active material layer and a negative electrode current collector, the negative electrode active material layer contains a negative electrode active material, a sulfide solid electrolyte, and a molten salt having a melting point of 30° C. or more and 80° C. or less, and the negative electrode current collector is a current collector in which a sulfidation reaction occurs due to the sulfide solid electrolyte.

[0007] According to the present disclosure, since the negative electrode active material layer contains a specified molten salt, even when a specified negative electrode current collector is used, an all-solid-state battery is obtained in which an increase in internal resistance is suppressed.

[0008] In the above disclosure, the molten salt may have an ammonium-based cation.

[0009] In the above disclosure, the molten salt may further include Li ions.

[0010] In the above disclosure, the molten salt may have an anion having a sulfonyl amide structure.

[0011] In the above disclosure, the negative electrode active material layer may contain tetrabutylammonium bis(trifluoromethanesulfonyl)amide and lithium bis(trifluoromethanesulfonyl)amide as the molten salt.

[0012] In the above disclosure, the negative electrode current collector may contain at least one element selected from the group consisting of Ni, Fe, and Cu.

[0013] In the above disclosure, the negative electrode current collector may be a metal foil having a rough surface.

[0014] In the above disclosure, the negative electrode active material layer does not have to contain granules having the negative electrode active material and the molten salt. Effect of the Invention

[0015] The present disclosure has an effect of providing an all-solid-state battery in which an increase in internal resistance is suppressed. [Brief description of the drawings]

[0016] [Figure 1] FIG. 1 is a schematic cross-sectional view illustrating an all-solid-state battery according to the present disclosure. [Diagram 2] 1 shows the results of resistance increase rates for the evaluation batteries obtained in Example 1 and Comparative Example 1. [Diagram 3] 1 shows the results of SEM observation of the evaluation batteries obtained in Example 1 and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] The all-solid-state battery according to the present disclosure will be described in detail below.

[0018] FIG. 1 is a schematic cross-sectional view illustrating an all-solid-state battery according to the present disclosure. The all-solid-state battery 10 shown in FIG. 1 has a positive electrode (CA) having a positive electrode active material layer 1 and a positive electrode current collector 2, a negative electrode (AN) having a negative electrode active material layer 3 and a negative electrode current collector 4, and a solid electrolyte layer 5 disposed between the positive electrode active material layer 1 and the negative electrode active material layer 3. The negative electrode active material layer 3 contains a negative electrode active material, a sulfide solid electrolyte, and a molten salt having a melting point of 30° C. or more and 80° C. or less. The negative electrode current collector 4 is a current collector in which a sulfurization reaction occurs due to the sulfide solid electrolyte contained in the negative electrode active material layer 3.

[0019] According to the present disclosure, since the negative electrode active material layer contains a predetermined molten salt, even when a predetermined negative electrode current collector is used, an all-solid-state battery in which an increase in internal resistance is suppressed is obtained. As described above, when the negative electrode active material layer contains a sulfide solid electrolyte, the sulfide solid electrolyte may react with the negative electrode current collector, causing the negative electrode current collector to be sulfurized. When the negative electrode current collector is sulfurized, the internal resistance increases and the battery performance decreases. In particular, when charging and discharging are repeated, the internal resistance increases over time and the battery performance is significantly reduced. In contrast, it is presumed that the molten salt in the present disclosure functions as a so-called sacrificial material and protects the negative electrode current collector. Therefore, it is presumed that the sulfurization (chemical corrosion) of the negative electrode current collector can be suppressed, and the increase in internal resistance can be suppressed.

[0020] 1.Negative electrode The negative electrode in the present disclosure has a negative electrode active material layer and a negative electrode current collector.

[0021] (1) Negative electrode active material layer The negative electrode active material layer in the present disclosure contains a negative electrode active material, a sulfide solid electrolyte, and a molten salt.

[0022] (i) Molten salt The molten salt in the present disclosure usually has a melting point of 30° C. or higher and 80° C. or lower. The molten salt in the present disclosure corresponds to an ionic compound that is in a solid state at 25° C. (room temperature) and is different from an ionic liquid (room temperature ionic liquid, RTIL) that is in a liquid state at 25° C. The melting point of the molten salt may be 40° C. or higher, or may be 50° C. or higher. On the other hand, the melting point of the molten salt may be, for example, 70° C. or lower.

[0023] The molten salt has a cation and an anion. Examples of the cation include inorganic cations such as lithium ion, sodium ion, potassium ion, and cesium ion; and organic cations such as ammonium-based cations, piperidinium-based cations, pyrrolidinium-based cations, imidazolium-based cations, pyridinium-based cations, alicyclic amine-based cations, aliphatic amine-based cations, and aliphatic phosphonium-based cations. The molten salt may have only one type of cation, or may have two or more types. The molten salt may also have both inorganic and organic cations.

[0024] The molten salt preferably has an ammonium-based cation. The ammonium-based cation is, for example, a cation represented by the general formula: + It is preferable that the molten salt is represented by R1R2R3R4 (R1 to R4 are each independently a hydrocarbon group). Examples of the hydrocarbon group include a saturated hydrocarbon group, an unsaturated hydrocarbon group, and an aromatic hydrocarbon group. The hydrocarbon group may be an alkyl group. The number of carbon atoms in the hydrocarbon group may be, for example, 1, 2, 3, 4, or 5 or more. On the other hand, the number of carbon atoms in the hydrocarbon group is, for example, 10 or less. The ammonium cation may be a tetrabutylammonium ion, or may not be a tetrabutylammonium ion. In addition, it is preferable that the molten salt has a Li ion. In particular, it is preferable that the molten salt has both a Li ion and an ammonium cation.

[0025] The anion of the molten salt may be, for example, an anion having a sulfonylamide structure. The anion having a sulfonylamide structure may be, for example, bis(trifluoromethanesulfonyl)amide, bis(fluorosulfonyl)amide, bis(pentafluoroethanesulfonyl)amide, (fluorosulfonyl)(trifluoromethanesulfonyl)amide. The molten salt may have only one type of anion, or may have two or more types.

[0026] The molten salt preferably contains at least lithium bis(trifluoromethanesulfonyl)amide (Li-TFSA), and may contain lithium bis(trifluoromethanesulfonyl)amide (Li-TFSA) and tetrabutylammonium bis(trifluoromethanesulfonyl)amide (TBA-TFSA). The molar ratio of TBA-TFSA to Li-TFSA is, for example, 0.5 or more, may be 1 or more, or may be 2 or more. On the other hand, the molar ratio is, for example, 100 or less, and may be 50 or less.

[0027] The molten salt preferably contains at least lithium bis(fluorosulfonyl)amide (Li-FSA), and may contain lithium bis(fluorosulfonyl)amide (Li-FSA) and cesium bis(fluorosulfonyl)amide (Cs-FSA). The molar ratio of Cs-FSA to Li-FSA is, for example, 0.5 or more, may be 1 or more, or may be 2 or more. On the other hand, the molar ratio is, for example, 100 or less, and may be 50 or less.

[0028] The molten salt may also have a first imidazolium salt having a cation represented by general formula (1) and an anion which is MX4 (M is a transition metal and X is a halogen), and a second salt having a monovalent cation and a halogen.

[0029] The first imidazolium salt has a cation represented by general formula (1).

[0030] [ka]

[0031] In general formula (1), R1 and R2 are each an alkyl group having 1 to 10 carbon atoms, and may be an alkyl group having 1 to 4 carbon atoms. Examples of the alkyl group include an ethyl group, a methyl group, a propyl group, and a butyl group. R1 and R2 may be the same or different from each other.

[0032] The first imidazolium salt has MX4 (M is a transition metal, X is a halogen). Examples of M include Fe, Cr, V, Co, Mn, Ti, Ru, and Pb. On the other hand, examples of X include F, Cl, Br, and I. The valence of M in MX4 is preferably divalent or trivalent.

[0033] On the other hand, the second salt has a monovalent cation. An example of the monovalent cation is a cation represented by the general formula (2).

[0034] [ka]

[0035] In the general formula (2), R3 and R4 are the same as R1 and R2 described above, and therefore the description thereof is omitted here. In addition, R3 may be the same as R1, and R4 may be the same as R2.

[0036] Other examples of the monovalent cation in the second salt include alkali metal ions such as lithium ion, sodium ion, and potassium ion.

[0037] The second salt also has a halogen. Examples of the halogen in the second salt include F, Cl, Br, and I.

[0038] The ratio of the first imidazolium salt and the second salt in the molten salt is not particularly limited, but when the first imidazolium salt is taken as 100 parts by mole, the ratio of the second salt is, for example, 100 parts by mole or less, or may be 80 parts by mole or less, or may be 50 parts by mole or less, while the ratio of the second salt is, for example, 1 part by mole or more.

[0039] The molten salt preferably has high Li-ion conductivity. The Li-ion conductivity of the molten salt at 25° C. is, for example, 1×10 -6 S / cm or more, 1×10 -5The molten salt may have a high electronic conductivity of 100 S / cm or more.

[0040] The ratio of the molten salt in the negative electrode active material layer is not particularly limited. In the negative electrode active material layer, when the negative electrode active material is 100 parts by weight, the molten salt is, for example, 1 part by weight or more, may be 5 parts by weight or more, or may be 10 parts by weight or more. On the other hand, when the negative electrode active material is 100 parts by weight, the molten salt is, for example, 30 parts by weight or less, may be 20 parts by weight or less, or may be 15 parts by weight or less. In addition, when the negative electrode active material is 100 parts by weight, the molten salt may be more than 30 parts by weight.

[0041] (ii) Negative electrode active material The negative electrode active material in the present disclosure is not particularly limited, and a known negative electrode active material can be used. The negative electrode active material is, for example, a Si-based active material. The Si-based active material is an active material containing an Si element. Examples of the Si-based active material include a simple Si element, an Si alloy, and an Si oxide. The Si alloy preferably contains an Si element as a main component. On the other hand, the negative electrode active material layer does not need to contain an Si-based active material. Examples of negative electrode active materials other than the Si-based active material include Li-based active materials such as metallic lithium and lithium alloys; carbon-based active materials such as graphite, hard carbon, and soft carbon; and oxide-based active materials such as lithium titanate.

[0042] The shape of the negative electrode active material may be, for example, particulate. 50 ) is not particularly limited, but is, for example, 10 μm or less, may be 5 μm or less, or may be 2 μm or less. On the other hand, the average particle size (D 50 ) is, for example, 0.1 μm or more. 50 ) is the cumulative 50% particle size (median size) and can be calculated, for example, from measurements using a laser diffraction particle size distribution analyzer or a scanning electron microscope (SEM).

[0043] The ratio of the negative electrode active material in the negative electrode active material layer is, for example, 40% by weight or more, or may be 50% by weight or more, or may be 60% by weight or more, while the ratio of the negative electrode active material in the negative electrode active material layer is, for example, 95% by weight or less.

[0044] (iii) Sulfide solid electrolyte The negative electrode active material layer contains a sulfide solid electrolyte. The sulfide solid electrolyte usually contains sulfur (S) as a main component of an anion element. The sulfide solid electrolyte preferably contains, for example, Li element, X element (X is at least one of P, As, Sb, Si, Ge, Sn, B, Al, Ga, and In), and S element. The sulfide solid electrolyte may also contain at least one of Cl element, Br element, and I element as a halogen element. The sulfide solid electrolyte may also contain O element.

[0045] The sulfide solid electrolyte may be a glass-based sulfide solid electrolyte, a glass ceramic-based sulfide solid electrolyte, or a crystalline sulfide solid electrolyte. In addition, when the sulfide solid electrolyte has a crystalline phase, examples of the crystalline phase include a Thio-LISICON type crystalline phase, a LGPS type crystalline phase, and an Argyrodite type crystalline phase.

[0046] The composition of the sulfide solid electrolyte is not particularly limited, but examples thereof include xLi2S·(100-x)P2S5 (70≦x≦80), yLiI·zLiBr·(100-yz)(xLi2S·(1-x)P2S5) (0.7≦x≦0.8, 0≦y≦30, 0≦z≦30).

[0047] The sulfide solid electrolyte has the general formula: Li 4-x Ge 1-x P xIt may have a composition represented by S4(0 < x < 1). In the above general formula, at least a part of Ge may be substituted with at least one of Sb, Si, Sn, B, Al, Ga, In, Ti, Zr, V, and Nb. In the above general formula, at least a part of P may be substituted with at least one of Sb, Si, Sn, B, Al, Ga, In, Ti, Zr, V, and Nb. In the above general formula, a part of Li may be substituted with at least one of Na, K, Mg, Ca, and Zn. In the above general formula, a part of S may be substituted with a halogen (at least one of F, Cl, Br, and I).

[0048] As other compositions of the sulfide solid electrolyte, for example, Li 7-x-2y PS 6-x-y X y , Li 8-x-2y SiS 6-x-y X y , Li 8-x-2y GeS 6-x-y X y may be mentioned. In these compositions, X is at least one of F, Cl, Br, and I, and x and y satisfy 0 ≤ x, 0 ≤ y.

[0049] The sulfide solid electrolyte preferably has a high Li-ion conductivity. The Li-ion conductivity of the sulfide solid electrolyte at 25°C is, for example, 1×10 -4 S / cm or more, and preferably 1×10 -3 S / cm or more. Also, as the shape of the sulfide solid electrolyte, for example, particulate form may be mentioned. The average particle size (D 50 ) of the sulfide solid electrolyte is, for example, 0.1 μm or more and 50 μm or less.

[0050] (iv) Negative electrode active material layer The negative electrode active material layer may or may not contain granules having a negative electrode active material and a molten salt. A plurality of negative electrode active material particles are aggregated via the molten salt to form a granule. Whether or not the negative electrode active material layer contains granules can be determined, for example, by observing a cross section of the negative electrode active material layer by scanning electron microscope-energy dispersive X-ray measurement (SEM-EDX measurement). Specifically, when it is confirmed based on a cross-sectional EDX analysis that an element contained in the negative electrode active material and a constituent element of the molten salt are concentrated in the same place, and further based on an image analysis of a cross-sectional SEM image that particles of the negative electrode active material are aggregated, it can be determined that the negative electrode active material layer contains granules. On the other hand, when the above case does not apply, it can be determined that the negative electrode active material layer does not contain granules. The granules may or may not contain a binder. The granules may not contain a solid electrolyte. Similarly, the granules may not contain a conductive material.

[0051] The negative electrode active material layer may further contain at least one of a conductive material and a binder. Examples of the conductive material include carbon materials, metal particles, and conductive polymers. Examples of the carbon material include particulate carbon materials such as acetylene black (AB) and ketjen black (KB), and fibrous carbon materials such as carbon fibers, carbon nanotubes (CNT), and carbon nanofibers (CNF). Examples of the binder include fluorine-containing binders such as polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE), rubber-based binders such as butadiene rubber, and acrylic binders. The thickness of the negative electrode active material layer is, for example, 0.1 μm or more and 1000 μm or less.

[0052] (2) Negative electrode current collector The negative electrode current collector is a member that collects the current from the negative electrode active material layer. The negative electrode current collector is disposed, for example, on the surface of the negative electrode active material layer opposite to the solid electrolyte layer. The negative electrode current collector is a current collector in which a sulfide reaction occurs due to a sulfide solid electrolyte. Whether or not the negative electrode current collector is a "negative electrode current collector in which a sulfide reaction occurs due to a sulfide solid electrolyte" is determined, for example, by the method described in the comparative example described later. Specifically, a test battery that does not contain a molten salt is produced, a durable charge / discharge test is performed, and then the surface of the negative electrode current collector is observed to determine whether or not the negative electrode current collector is a "negative electrode current collector in which a sulfide reaction occurs due to a sulfide solid electrolyte."

[0053] The negative electrode current collector usually contains a metal element. Examples of the metal element include Ni, Fe, and Cu. The negative electrode current collector may be a single metal or a metal alloy. The metal alloy may be an alloy mainly composed of Ni, an alloy mainly composed of Fe, or an alloy mainly composed of Cu. For example, an "alloy mainly composed of Ni" means that the atomic ratio of Ni is the highest in the alloy. The same applies to other alloys. An example of an alloy mainly composed of Fe is stainless steel (SUS).

[0054] The negative electrode current collector may be a metal foil having a rough surface (typically, a roughened metal foil). A metal foil having a rough surface refers to a metal foil having a surface roughness Rz of 1.5 μm or more. When the negative electrode current collector has a rough surface, valleys are formed on the surface of the negative electrode current collector, so that the molten salt is likely to wet and spread over the surface of the negative electrode current collector. As a result, the negative electrode current collector is effectively protected by the molten salt, and corrosion of the negative electrode current collector can be suppressed. The surface roughness Rz of the negative electrode current collector may be 2.0 μm or more, or may be 3.0 μm or more. On the other hand, the surface roughness Rz is, for example, 10 μm or less. The surface roughness Rz refers to the maximum height roughness, and corresponds to the sum of the highest part (maximum peak height: Rp) and the deepest part (maximum valley depth: Rv) of a part of a roughness curve measured by a roughness meter, which is extracted over a reference length. In addition, the shape of the negative electrode current collector may be, for example, a foil shape or a mesh shape.

[0055] 2.Positive electrode The positive electrode in the present disclosure generally includes a positive electrode active material layer and a positive electrode current collector. The positive electrode active material layer is a layer containing at least a positive electrode active material. The positive electrode active material layer may contain at least one of a solid electrolyte, a conductive material, and a binder, as necessary.

[0056] The positive electrode active material is typically an oxide active material. Examples of the oxide active material include LiCoO2, LiMnO2, LiNiO2, LiVO2, and LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, etc., rock salt layered active materials, LiMn2O4, Li(Ni 0.5 Mn 1.5 )O4 and the like; and olivine type active materials such as LiFePO4, LiMnPO4, LiNiPO4, and LiCuPO4.

[0057] The surface of the positive electrode active material may be coated with a coating layer. The coating layer can suppress the reaction between the positive electrode active material and the solid electrolyte (particularly the sulfide solid electrolyte). Examples of the coating layer include Li-containing oxides such as LiNbO3, Li3PO4, and LiPON. The average thickness of the coating layer is, for example, 1 nm or more. On the other hand, the average thickness of the coating layer is, for example, 20 nm or less, and may be 10 nm or less.

[0058] The solid electrolyte, conductive material, and binder used in the positive electrode active material layer are the same as those described in "1. Negative electrode" above, so the description here is omitted. The thickness of the positive electrode active material layer is, for example, 0.1 μm or more and 1000 μm or less.

[0059] The positive electrode current collector is a member that collects the current from the positive electrode active material layer. The positive electrode current collector is disposed, for example, on the surface of the positive electrode active material layer opposite to the solid electrolyte layer. Examples of the material for the positive electrode current collector include Al, SUS, and Ni. Examples of the shape of the positive electrode current collector include a foil shape and a mesh shape.

[0060] 3.Solid electrolyte layer The solid electrolyte layer in the present disclosure is a layer disposed between a positive electrode and a negative electrode. Specifically, the solid electrolyte layer is disposed between a positive electrode active material layer in the positive electrode and a negative electrode active material layer in the negative electrode. The solid electrolyte layer contains at least a solid electrolyte. The solid electrolyte layer may further contain a binder as necessary. The solid electrolyte and the binder are the same as those described in "1. Negative electrode" above, and therefore the description here is omitted. The thickness of the solid electrolyte layer is, for example, 0.1 μm or more and 1000 μm or less.

[0061] 4.All-solid-state battery The all-solid-state battery according to the present disclosure may have an exterior body that houses the positive electrode, the solid electrolyte layer, and the negative electrode. The exterior body may be a laminate type exterior body or a case type exterior body.

[0062] The all-solid-state battery in the present disclosure may have a restraining jig that applies a restraining pressure to the positive electrode, the solid electrolyte layer, and the negative electrode along the thickness direction. By applying the restraining pressure, a good ion conduction path and an electron conduction path are formed. The restraining pressure is, for example, 0.1 MPa or more, may be 1 MPa or more, or may be 5 MPa or more. On the other hand, the restraining pressure is, for example, 100 MPa or less, may be 50 MPa or less, or may be 20 MPa or less. The type of the restraining jig is not particularly limited, but examples thereof include a restraining jig that applies a restraining torque by a bolt.

[0063] The type of all-solid-state battery in the present disclosure is not particularly limited, but is typically an all-solid-state lithium-ion secondary battery. Applications of the all-solid-state battery include, for example, power sources for vehicles such as hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), electric vehicles (BEVs), gasoline-powered vehicles, and diesel-powered vehicles. In particular, it is preferable to use the all-solid-state battery as a driving power source for hybrid electric vehicles or electric vehicles. In addition, the all-solid-state battery in the present disclosure may be used as a power source for moving objects other than vehicles (for example, railways, ships, and aircraft), and may be used as a power source for electrical products such as information processing devices.

[0064] The present disclosure is not limited to the above-described embodiment. The above-described embodiment is merely an example, and any configuration that is substantially the same as the technical idea described in the claims of the present disclosure and that exhibits similar effects is included in the technical scope of the present disclosure. EXAMPLES

[0065] [Example 1] (Preparation of positive electrode) A mixture containing a positive electrode active material (NCA-based positive electrode active material), a sulfide solid electrolyte (Li2S-P2S5-based sulfide solid electrolyte), a conductive material (vapor-phase grown carbon fiber), a binder (PVdF-based binder), and a dispersion medium (butyl butyrate) as raw materials was stirred by an ultrasonic dispersion device to prepare a positive electrode slurry. Here, the weight ratio of the positive electrode active material:sulfide solid electrolyte:conductive material:binder was 100:16:2:0.75. This positive electrode slurry was applied onto a positive electrode current collector (Al foil) by the blade method, and dried on a hot plate at 100°C for 30 minutes. As a result, a positive electrode having a positive electrode current collector and a positive electrode active material layer was obtained.

[0066] (Synthesis of molten salt) Tetrabutylammonium bis(trifluoromethanesulfonyl)amide (TBA-TFSA) and lithium bis(trifluoromethanesulfonyl)amide (Li-TFSA) were prepared as raw materials. Next, TBA-TFSA and Li-TFSA were heated and mixed in a molar ratio of 1:1 to obtain a molten salt. Differential scanning calorimetry (DSC measurement) was performed on the obtained molten salt at a rate of 1°C / min. As a result, the melting point of the molten salt was 56°C, and it was in a solid state at room temperature (25°C). The melting points of TBA-TFSA and Li-TFSA are 90°C and 235°C, respectively.

[0067] (Preparation of negative electrode) A mixture containing the raw material anode active material (Si particles), synthesized molten salt, sulfide solid electrolyte (Li2S-P2S5-based sulfide solid electrolyte), conductive material (vapor-phase grown carbon fiber), binder (BR-based binder) and dispersion medium (diisobutyl ketone) was stirred using a thin-film rotating high-speed mixer (Filmix) to prepare anode slurry. Here, the weight ratio of Si particles: molten salt: sulfide solid electrolyte: conductive material: binder was 100: 11.5: 76: 15: 4. This anode slurry was applied to an anode current collector (roughened Ni foil, Rz = 2.0 μm) by the blade method and dried on a hot plate at 100 ° C for 30 minutes. As a result, anode having an anode current collector and an anode active material layer was obtained.

[0068] (Preparation of solid electrolyte layer) A solid electrolyte mixture containing a sulfide solid electrolyte (Li2S-P2S5-based sulfide solid electrolyte), a binder (PVdF-based binder), and a dispersion medium (butyl butyrate) as raw materials was stirred with an ultrasonic dispersing device to prepare a solid electrolyte slurry. Here, the weight ratio of the sulfide solid electrolyte to the binder was set to 99.6:0.4. This solid electrolyte slurry was applied onto an Al foil by the blade method and dried on a hot plate at 100°C for 30 minutes to obtain a peelable solid electrolyte layer.

[0069] (Preparation of Positive Electrode Laminate) The positive electrode active material layer of the positive electrode and the peelable solid electrolyte layer were laminated so that the composite surfaces overlapped. They were pressed using a roll press under conditions of a pressure of 50 kN / cm and a temperature of 160°C, after which the Al foil of the solid electrolyte layer was peeled off and a 1 cm 2 A positive electrode laminate was obtained by punching out the laminate into a size of 10 mm.

[0070] (Preparation of negative electrode laminate) The negative electrode active material layer of the negative electrode and the peelable solid electrolyte layer were laminated so that the composite surfaces overlapped. They were pressed using a roll press under conditions of a pressure of 50 kN / cm and a temperature of 160°C, after which the Al foil of the solid electrolyte layer was peeled off, and the laminate was separated into 1.08 cm 2A negative electrode laminate was obtained by punching out the negative electrode laminate to a size of 1.08 cm. The solid electrolyte layer of the negative electrode laminate and the peelable solid electrolyte layer were then laminated so that the composite surfaces overlapped. This laminate was pre-pressed using a flat uniaxial press under conditions of a pressure of 100 MPa and a temperature of 25°C. The Al foil of the solid electrolyte layer was then peeled off, and the laminate was cut into pieces of 1.08 cm. 2 By punching out the resulting sheet, a negative electrode laminate having an additional solid electrolyte layer was obtained.

[0071] (Preparation of evaluation battery) The positive electrode laminate and the negative electrode laminate having an additional solid electrolyte layer were laminated so that the composite surfaces overlapped. This laminate was pressed using a flat uniaxial press under conditions of a pressure of 200 MPa and a temperature of 120°C to obtain a battery laminate. The obtained battery laminate was sandwiched between two restraining plates, and these two restraining plates were clamped with a fastener at a restraining pressure of 10 MPa to produce an evaluation battery.

[0072] [Comparative Example 1] A battery for evaluation was produced in the same manner as in Example 1, except that the negative electrode was produced without using molten salt. Specifically, a negative electrode mixture containing a negative electrode active material (Si particles), a sulfide solid electrolyte (Li2S-P2S5-based sulfide solid electrolyte), a conductive material (vapor-phase grown carbon fiber), a binder (BR-based binder), and a dispersion medium (diisobutyl ketone) as raw materials was stirred using a thin-film rotating high-speed mixer (Filmix) to produce a negative electrode slurry. Here, the weight ratio of Si particles:sulfide solid electrolyte:conductive material:binder was set to 100:87.5:15:4. A battery for evaluation was produced in the same manner as in Example 1, except that the obtained negative electrode slurry was used.

[0073] [evaluation] (Charge / discharge test) A charge / discharge test was performed on the evaluation batteries obtained in Example 1 and Comparative Example 1. First, the initial charge / discharge was performed under the following conditions: constant current charging at 1 / 10C up to 4.05V, followed by constant voltage charging at 4.05V up to a cut-off current of 1 / 100C. Next, constant current discharging at 1 / 10C up to 2.5V, followed by constant voltage discharging up to 2.5V up to a cut-off current of 1 / 100C.

[0074] Next, the initial resistance was measured. That is, the battery was charged at a constant current of 1 / 10 C to 3.0 V, and then charged at a constant voltage of 3.0 V to a final current of 1 / 100 C to adjust the state of charge. After adjusting the state of charge, the impedance was measured at room temperature, and the DC resistance was calculated from the circular component on the high frequency side.

[0075] Next, as a durability charge / discharge cycle, charge / discharge was repeated 100 times under the following conditions. Durable charging: 1C, constant current charging up to 4.05V Durability discharge: 1C, constant current discharge up to 2.5V

[0076] Next, resistance was measured after the durability test. That is, the battery was charged at a constant current of 1 / 10C up to 3.0V, and then charged at a constant voltage of 3.0V up to a cut-off current of 1 / 100C to adjust the state of charge. After adjusting the state of charge, the impedance was measured at room temperature, and the DC resistance was calculated from the arc component on the high frequency side. The ratio of the DC resistance at the 100th cycle to the DC resistance at the 1st cycle was calculated as the resistance increase rate (%). The results are shown in Figure 2.

[0077] 2, it was confirmed that the resistance increase rate of Example 1 (1.16%) was smaller than that of Comparative Example 1 (1.25%), and the increase in internal resistance was suppressed. This is presumably because the molten salt functioned as a sacrificial material.

[0078] (SEM observation) The negative electrode current collector of the evaluation battery after the durability test was observed with a scanning electron microscope (SEM). The results are shown in FIG. 3. As shown in FIG. 3(a), in Comparative Example 1, it was confirmed that NiS (a reaction product between Ni and a sulfide solid electrolyte) covered the Ni surface. In Comparative Example 1, it is presumed that Ni constituting the negative electrode current collector was corroded by sulfur components over time. When NiS is generated, it becomes a resistor and prevents electron transfer between the negative electrode current collector and the negative electrode active material layer. It is presumed that the internal resistance of the battery increased. On the other hand, in Example 1, it was not confirmed that NiS covered the Ni surface. In Example 1, it is presumed that the molten salt functions as a sacrificial material and protects the surface of the negative electrode current collector, thereby suppressing corrosion by sulfur components over time. In this way, it was confirmed that the increase in internal resistance can be suppressed by using a predetermined molten salt for the negative electrode active material layer. In addition, since the sulfurization reaction of the negative electrode current collector is a reaction between the negative electrode current collector and the sulfide solid electrolyte, it is presumed that it is not affected by the type of negative electrode active material. Therefore, even if an active material other than Si is used as the negative electrode active material, it is presumed that the increase in internal resistance can be suppressed by using a specific molten salt. [Explanation of symbols]

[0079] 1...Cathode active material layer 2...Positive electrode current collector 3...Negative electrode active material layer 4...Negative electrode current collector 5...Solid electrolyte layer 10...All-solid-state battery

Claims

1. An all-solid-state battery having a positive electrode, a negative electrode, and a solid electrolyte layer disposed between the positive electrode and the negative electrode, the negative electrode has a negative electrode active material layer and a negative electrode current collector, The negative electrode active material layer contains a negative electrode active material, a sulfide solid electrolyte, and a molten salt having a melting point of 30° C. or more and 80° C. or less, The negative electrode current collector is a current collector in which a sulfurization reaction occurs due to the sulfide solid electrolyte, and The all-solid-state battery, wherein the molten salt contains tetrabutylammonium bis(trifluoromethanesulfonyl)amide and lithium bis(trifluoromethanesulfonyl)amide.

2. The all-solid-state battery according to claim 1 , wherein the negative electrode current collector contains at least one element selected from the group consisting of Ni, Fe, and Cu.

3. The all-solid-state battery according to claim 1 or 2, wherein the negative electrode current collector is a metal foil having a rough surface.

4. The all-solid-state battery according to claim 1 , wherein the negative electrode active material layer does not contain granules having the negative electrode active material and the molten salt.

Citation Information

Patent Citations

  • Lithium polymer battery and its manufacturing method

    JP2006049158A

  • Manufacturing method of electrode for storage device and storage device

    JP2011151143A

  • Negative electrode active material particle and method for manufacturing negative electrode active material particle

    JP2017050109A

  • All-solid battery

    JP2019071244A

  • Negative electrode

    JP2020087783A